1992
DOI: 10.1007/bf02403821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcination, sintering and composition upon microwave properties of the Ba6−xSm8+2x/3Ti18O54-type oxide

Abstract: Dielectric ceramic compositions for microwave applications belonging to the (BaO) (Sm203) (Ti02) ternary phase diagram were studied. Calcination, sintering, microwave properties and influence of secondary phases were investigated. By varying composition and/or sintering process, a high dielectric constant with low dielectric losses and modulable negative or positive temperature coefficient of the resonant frequency can be reach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The density increases considerably with the sintering temperature up to 1300 • C, then, levels off above this temperature. The trend of densification curves are consistent with those reported by Laffez et al 26,28 and Ohsato et al 23 Comparing the densification results for y = 0, 0.5, and 1.0 (corresponding to Ba 6 − 3x Sm 8 + 2x Ti 18 O 54 , Ba 6 − 3x (Sm 0.5 Nd 0.5 ) 9 Ti 18 O 54 , and Ba 6 − 3x Nd 8 + 2x Ti 18 O 54 , respectively) shown in Fig. 1, the ceramics with y = 0 [Ba 6 − 3x Sm 8 + 2x Ti 18 O 54 ] generally has a higher densification, and ceramics with y = 1.0 [Ba 6 − 3x Nd 8 + 2x Ti 18 O 54 ] are inferior to the others.…”
Section: Densificationsupporting
confidence: 92%
“…The density increases considerably with the sintering temperature up to 1300 • C, then, levels off above this temperature. The trend of densification curves are consistent with those reported by Laffez et al 26,28 and Ohsato et al 23 Comparing the densification results for y = 0, 0.5, and 1.0 (corresponding to Ba 6 − 3x Sm 8 + 2x Ti 18 O 54 , Ba 6 − 3x (Sm 0.5 Nd 0.5 ) 9 Ti 18 O 54 , and Ba 6 − 3x Nd 8 + 2x Ti 18 O 54 , respectively) shown in Fig. 1, the ceramics with y = 0 [Ba 6 − 3x Sm 8 + 2x Ti 18 O 54 ] generally has a higher densification, and ceramics with y = 1.0 [Ba 6 − 3x Nd 8 + 2x Ti 18 O 54 ] are inferior to the others.…”
Section: Densificationsupporting
confidence: 92%
“…According to previous works, ST ceramic is formed when the sintering temperature of the specimen with the nominal composition of BST is lower than 1150 • C. 16 On the other hand, when the sintering temperature of the specimen exceeds 1150 • C, BST ceramic is formed. 17 Therefore, ST phase is considered to be a low temperature phase of BST ceramics, which is formed when the sintering temperature is not high enough to sinter the BST phase. These results can be used to explain the phase changes, which occurred in the BST films with respect to the growth temperature.…”
Section: Resultsmentioning
confidence: 99%
“…A sintering temperature of 1350-1370 • C is needed to obtain a ceramic disc with good dielectric properties of k = 105 and Q = 1000 at 1 MHz, however, the temperature coefficient of resonant frequency (τ f ) is very high (−104 ppm/ • C). Laffez [5] sintered BaO-(Nd 2 O 3 , Sm 2 O 3 )-TiO 2 system at 1400 • C and obtained a k of 74 to 81, a Q × f of up to 9000 GHz at 3 GHz, and a τ f of around +9 ppm/ • C. They found that addition of 1 or 2 wt% WO 3 , MnO 2 , and CaO to two compositions of the BaO-(Nd 2 O 3 , Sm 2 O 3 )-TiO 2 system densified ceramics and improved the microwave properties. The WO 3 and MnO doped ceramics show a large dielectric constant, accompanied second phase and lower Q × f value, however, the sintering temperatures are above 1350 • C.…”
Section: Introductionmentioning
confidence: 98%